Seroprevalence of Neospora caninum Infection in Rural and Industrial Cattle in Northern Iran - MR Youssefi; F Arabkhazaeli; A Tabar Molla Hassan (Iranian Journal of Parasitology, 2009)
Background: Neospora caninum is an intracellular parasite which causes abortion in cattle worldwide.  The aim of this study was to determine the seroprevalence of N. caninum in cattle in Babol City, North of Iran. Methods: Blood samples were collected from 237 cattle for determining the seroprevalence of N.  caninum.  A total of 237 serum samples were tested for anti-Neospora antibodies.  Serum samples were analyzed for antibodies against N. caninum antigen using a commercial N. caninum ELISA kit. Results: Antibodies to N. caninum were found in 76 of 237 total cattle (32%), 40 of 155 industrial cattle (25. 8%) and 36 of 82 rural cattle sera (43. 9%) based on ELISA test results. Conclusion: This study is the first report of Neospora infection in this area.  Significant difference was observed regarding infection in industrial and rural cattle (P<0. 01).